Modification of a natural zeolite with Fe(III) for simultaneous phosphate and ammonium removal from aqueous solutions - Guaya Caraguay, D. (2016)
BACKGROUND: The incorporation of Fe(III) was performed in a natural clinoptilolite (Z-N) for simultaneous phosphate and ammonium removal. RESULTS: The existence of hydroxyl groups (?Fe-OH) in the iron zeolite (Z-Fe) enhances the phosphate uptake from 0.60.1mg-P g-1 in Z-N to 3.40.2mg-P g-1 in Z-Fe. However, the ammonium sorption capacity slightly decreases from 332mg-Ng-1 in Z-N to 272mg-Ng-1 in Z-Fe. The equilibrium and kinetics sorption were well explained by the Langmuir isotherm and the intraparticle diffusion model, respectively. CONCLUSIONS: Both the phosphate and ammonium uptake were slightly affected by the coexistence of competing ions. The phosphate sorption capacity of iron zeolite was decreased in the regeneration cycles. Desorption using a 1molL-1 NaOH solution under dynamic conditions provided higher enrichment factors for ammonium than phosphate. © 2015 Society of Chemical Industry.